Improving Students' Problem-Solving Ability through E-Scaffolding in Inquiry Learning - Ovita Ardanari; Supriyono Koes H; Nandang Mufti (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: The purpose of this study was to analyze the effect of e-scaffolding on Newton’s law material on student’s problem solving abilities. This research uses a mixed-method type of explanatory design. Subjects in this study were 71 students of class X natural science program Senior High School 5 Malang, 35 students as the experimental group, and 36 students as the comparison group. The results showed that the problem-solving ability of students who received inquiry learning using e-scaffolding was 62.11 higher than students who learned using the usual method of 47.15. E-scaffolding conceptual-procedural provided helps students understand the concept of Newton’s law which guides and directs them to find solutions to a problem.Abstrak: Tujuan dari penelitian ini adalah menganalisis pengaruh pemberian e- scaffolding pada materi hukum Newton terhadap kemampuan pemecahan masalah siswa. Penelitian ini menggunakan mixed methods jenis explanatory design. Subjek penelitian adalah 71 siswa kelas X IPA SMA Negeri 5 Malang, 35 siswa sebagai kelompok eksperimen dan 36 siswa sebagai kelompok pembanding. Hasil penelitian menunjukkan bahwa kemampuan pemecahan masalah siswa yang mendapatkan pembelajaran inkuiri dengan e-scaffolding sebesar 62.11, lebih tinggi dibandingkan siswa yang belajar dengan metode biasa sebesar 47.15. E-scaffolding konseptual-prosedural yang diberikan membantu siswa memahami konsep hukum Newton dimana membimbing serta mengarahkan mereka untuk menemukan solusi dari sebuah masalah.